2017
DOI: 10.15761/rri.1000105
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoscintigraphy and clinic

Abstract: Lymphoedema is a clinically unusual picture characterized by slowing down or block of the lymphatic circulation of limb or limbs affected, with progressively worsening evolution and appearance of recurrent acute lymphangitis complications, responsible for a further increase in volume and consistency of edema. The diagnosis or early identification of lymphoedema as well as its predisposition, can be revealed by lymphoscintigraphy. The sentinel lymph node individuation and surgical removal can be considered to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In one study, it was found that total lymphatic obstruction was present in 56% of unilateral gynecological cancer-related lymphedema and that the stages of lymphoscintigraphy were statistically correlated with episodes of cellulite, circumferential difference and CT volume difference [15]. Lymphoscintigraphy is therefore an essential examination to establish the exact origin of the lymphatic block; this can be useful (often, indispensable) to establish the right therapy for the patient, and to agree together on a long-term maintenance path [16][17][18]. Some authors suggest that the deep circulation should also be studied with lymphoscintigraphy in patients with unilateral or bilateral lower limb lymphedema (LLE) (or sensation of LLE) without morphological or functional signs of lymphatic insufficiency, but whose history and clinical examination are indicative of the presence of lymphedema [19].…”
Section: Lymphoscintigraphymentioning
confidence: 99%
“…In one study, it was found that total lymphatic obstruction was present in 56% of unilateral gynecological cancer-related lymphedema and that the stages of lymphoscintigraphy were statistically correlated with episodes of cellulite, circumferential difference and CT volume difference [15]. Lymphoscintigraphy is therefore an essential examination to establish the exact origin of the lymphatic block; this can be useful (often, indispensable) to establish the right therapy for the patient, and to agree together on a long-term maintenance path [16][17][18]. Some authors suggest that the deep circulation should also be studied with lymphoscintigraphy in patients with unilateral or bilateral lower limb lymphedema (LLE) (or sensation of LLE) without morphological or functional signs of lymphatic insufficiency, but whose history and clinical examination are indicative of the presence of lymphedema [19].…”
Section: Lymphoscintigraphymentioning
confidence: 99%